TINJAUAN TEOLOGIS TENTANG SABAT BERDASARKAN KELUARAN 16:1-36 DAN IMPLIKASINYA BAGI GEREJA BETHEL INDONESIA HILISONDREKHA, TELUK DALAM - Mutiarni Bawaulu; Yudi Handoko (Sekolah Tinggi Teologi Duta Panisal, 2022)
The research in this thesis is motivated by the application of observing the Sabbath day, the congregation needs to understand and understand the Sabbath based on Exodus 16:1-36, the Sabbath is a day that God has given to humans to stop working, with the aim of humans enjoying themselves for six months. working day, and besides that God has also given this rest to humans so that humans remember the goodness of God while living on this earth, through fellowship in God's house or worship on the Sabbath. Seeing the importance of an observance in observing the Sabbath and understanding the congregation in observing the Sabbath, the congregation needs to know the meaning of the Sabbath which is based on Exodus 16:1-36. This study uses a qualitative method with a case study approach. Case studies or case studies are part of a qualitative method that wants to explore a particular case in greater depth by involving the collection of various sources of information. After conducting research and obtaining the results of interviews from the cases studied, the researchers used a descriptive approach to describe, explain and describe the data that had been obtained by the researchers from the interviews. The research findings in this thesis can be trusted for the validity of the data because they have gone through a scientific research process. The results of this study obtained data stating that the members of the Indonesian Bethel Church, Hilisondrekah, Teluk Dalam, did not understand the meaning of the Sabbath in observing the Sabbath.